2009
DOI: 10.1016/j.vaccine.2009.01.088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Signal 3 during CD8 T cell priming: Bystander production of IL-12 enhances effector T cell expansion but promotes terminal differentiation

Abstract: Adjuvants are commonly used in vaccines to augment immune response, but how the inflammatory cytokines elicited by adjuvants directly influence effector and memory CD8 T cell differentiation remains poorly characterized. Here, we used a peptide-pulsed dendritic cell (DC) vaccination model to examine the role of primary cytokines, IL-12 and IFNγ, elicited by CpG-B adjuvant on CD8 T cell priming and memory CD8 T cell development. During DC vaccination, simultaneous exposure to antigen and a heterologous Listeria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
135
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(148 citation statements)
references
References 45 publications
10
135
3
Order By: Relevance
“…It is well established that three signals are necessary for the activation of naïve CD8 + T cells: (i) TCR stimulation, (ii) costimulation, and (iii) inflammatory cytokines (15), but how variations in these signals may orchestrate effector and memory heterogeneity is not clear. Interestingly, alterations in the amount of antigenic exposure do not seem to skew effector cell differentiation, but the inflammatory milieu is able to alter the SLEC/MPEC ratio (12,14,16).…”
Section: Both Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that three signals are necessary for the activation of naïve CD8 + T cells: (i) TCR stimulation, (ii) costimulation, and (iii) inflammatory cytokines (15), but how variations in these signals may orchestrate effector and memory heterogeneity is not clear. Interestingly, alterations in the amount of antigenic exposure do not seem to skew effector cell differentiation, but the inflammatory milieu is able to alter the SLEC/MPEC ratio (12,14,16).…”
Section: Both Cd4mentioning
confidence: 99%
“…Although earlier work demonstrated that TCR or cytokine signaling alone were insufficient to up-regulate KLRG1 on T cells (39), recent work has shown that IL-12 signaling in the antigen-specific CD8 + T cells is important for SLEC differentiation and this process is T-bet mediated (12). Furthermore, inflammatory and IL-12 signaling events are temporally linked with TCR engagement (16). The transcription factor Blimp1 has been found to be important in the generation of SLEC (40,41).…”
Section: Cd40 Independent But Required Cd4mentioning
confidence: 99%
“…IFN-g is required to upregulate T-bet in CD8 + T cells in an indirect manner upon virus infection (12,41). We wondered whether the increased expression of T-bet in Roquin san/san mice is a consequence of excessive IFN-g. To assess this, we measured Tbet mean fluorescence intensity (MFI) in naive (CD44 lo ) CD8 + T cells and SLEC-like cells from Roquin san/san mice deficient or not in IFN-gR1.…”
Section: T-bet Reduction Delays the Onset Of Diabetesmentioning
confidence: 99%
“…2B). Interestingly, during this time, most cells retained high levels of CD127 (IL-7R), which is generally down-regulated upon CD8 T-cell activation (30) and did not up-regulate KLRG1, whose induction is linked to terminal differentiation (31,32).…”
Section: Endogenous Naïve Cd8 T Cells Undergo Robust Expansion But Notmentioning
confidence: 99%